Novel vs clinical organ preservation solutions: improved cardiac mitochondrial protection. Issue 1 (December 2017) - Ferng, Alice; Schipper, David; Connell, Alana; Marsh, Katherine; Knapp, Shannon; Khalpey, Zain
Abstract Background Heart transplantation remains the gold standard for end-stage heart failure, with current ex vivo organ storage times limited to 4 to 6 h before critical tissue damage occurs. Many preservation solutions exist in an attempt to limit both ischemic and reperfusion damage. In order to compare the effects of various storage solutions, mitochondrial function can be used to provide a sensitive analysis of cellular metabolic function. Methods Experimental plates were seeded with cardiac myoblasts and kept in suspended animation for either 4 or 8 h at either 4o or 21 °C, in Celsior®, Perfadex®, or Somah storage solutions. Cells were then reanimated for 1 h at 37 °C to simulate a reperfusion or clinical transplant scenario. Cellular bioenergetics were measured immediately thereafter to examine biochemical differences between preservation solutions and their effectiveness on preserving metabolic function. Results The oxygen consumption rates of Somah solution were significantly higher than Celsior® and Perfadex® at 4 °C, with the exception of Perfadex® at 4o for 4 h. This effect was sustained up to 8 h. At 21 °C, oxygen consumption rates of Somah solution are significantly higher than Celsior® and Perfadex® at basal conditions after 4 h, but this effect is not sustained after 8 h. Conclusions The purpose of this experiment was to study the efficacy of various preservation solutions on a mitochondrial level. The significantly higher oxygen consumption rates of Somah at 4 °C suggests that Somah solution may have the ability to protect cellular mitochondrial integrity, improve transplanted organ function by reducing ischemic-reperfusion injury, and thereby improve transplant outcomes. Given that Somah offers benefits over Celsior® and Perfadex® at 4 °C, it should be a target in future organ preservation solution research.